Benchmarking Reproductive Efficiency and Transition Cow Health of Kansas Dairy Herds - A. Scanavez; B. E. Voelz; L. Mendonca (Kansas Agricultural Experiment Station Research Reports, 2016)
Comparing key performance indicators across dairy farms may provide insightful information to dairy producers. Differences in management philosophies, facilities, and locations of dairy farms may influence overall performance of dairy operations. An ongoing extension program aims to benchmark reproductive performance and transition cow health of dairy farms located in Kansas and adjacent states. In this report, we compiled data from 2013 to 2015 of herds enrolled in the program and divided the data in warm and cool seasons to evaluate the impact of heat stress on key performance indicators. Annual pregnancy risk and warm to cool ratio of pregnancy risk varied from 20.9 to 22.5% and 75 to 82%, respectively. Annual insemination risk varied from 63.6 to 66.4% and warm to cool ratio of insemination risk varied from 96 to 97%, which suggests that heat stress does not remarkably affect insemination risk. In contrast, conception risk is significantly affected by heat stress because conception risk in the warm season ranged from 26.7 to 29.6% and in the cool season from 34.5 to 35.4% from 2013 to 2015. Percentage of cows that were treated for mastitis within 21 d after calving was below 4% annually. Warm to cool ratio of percentage of cows treated for mastitis ranged from 139 to 170%, indicating that during summer, cows are at increased risk of being affected by early postpartum mastitis. Benchmarking key performance indicators may assist dairy producers to identify areas of opportunity for improvement.
Keywords: dairy cattle; benchmarking; reproductive efficiency; cow health